Increasing Farmers' Knowledge and Skills through Socialization of EM4 (Effective Microorganism) Making in Kananga Village, Kuningan Regency: Peningkatan Pengetahuan Dan Keterampilan Petani Melalui Sosialisasi Pembuatan EM4 (Effective Microorganism) di Desa Kananga Kabupaten Kuningan - Setiawati, Ina; Nurlaelah, Ilah; Hindriana, Anna Fitri; Handayani, Handayani; Septiawati, Adevia; Nurdayanti, Rolanda Rasendriya (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Farmers in Kananga Village still use chemical fertilizers, this has led to farmers' dependence on chemical fertilizers. Farmers can make their own organic fertilizer, but farmers introduce time for the composting process to the materials that will be used as organic fertilizer. Farmers need technology that can accelerate the process of composting organic matter, and farmers also need to know the effect of chemical fertilizers on reducing soil fertility. Therefore, there is a need for community service activities that train and assist farmers to use organic fertilizer switching, and introduce Effective Microorganism 4 (EM4) technology in making fertilizer or EM4 in agriculture. EM4 is a technology for cultivating a mixture of microorganisms suitable for plant growth in agriculture. These microorganisms are bacteria that can be grown independently by the community, especially farmers in Kananga Village. This PkM activity is designed as an effort to reduce farmers' dependence on chemical fertilizers and invites farmers to use EM4 technology in making fertilizers. The results of this PkM also hope to make the community in Kananga Village more independent by being able to produce their own agricultural products in order to increase the competitiveness of the village. In addition, the PkM training and mentoring program is the commitment of the University of Kuningan in improving community empowerment. Abstrak Petani di Desa Kananga masih menggunkan pupuk kimia, hal ini menimbulkan kergantungan petani terhadap pupuk kimia. Petani dapat membuat pupuk organic sendiri, namun petani mengeluhkan lamanya waktu untuk proses pengomposan pada bahan bahan yang akan dijadikan pupuk organic. Petani perlu teknologi yang dapat mempercepat proses pengomposan bahan organic, dan petani juga perlu mengetahui dampak yang akan ditimbulkan dari pupuk kimia bisa merusak kesuburan tanah. Oleh karena itu kegiatan pengabdian masyarakat yang melatih dan mendampingi petani agar beralih menggunakan pupuk organic, serta mengenalkan teknologi Effective Microorganism 4 (EM4) dalam membuat pupuk ataupun EM4 dalam pertanian. EM4 ini merupakan teknologi dalam mengkultur campuran dari mikroorganisme yang menguntungkan untuk pertumbuhan tanaman dalam usaha pertanian. Mikkroorganisme tersebut merupakan bakteri-bakteri yang dapat dibibit secara mandiri oleh masyarakat khusunya para petani di Desa Kananga. Kegiatan PkM ini merupakan upaya menghilangkan ketergantungan petani terhadap pupuk kimia serta mengajak petani untuk menggunakan teknologi EM4 dalam membuat pupuknya. Hasil PkM ini juga berharap dapat menjadikan masyarakat di Desa Kananga menjadi semakin mandiri dengan mampu menghasilkan produk pertanian sendiri guna meningkatkan daya saing Desa. Program PkM ini melatih dan mendampingi masyarakat merupakan Visi Universitas Kuningan kearah pemberdayaan masyarakat.